POLA KOMUNIKASI ORGANISASI TRADISIONAL ( STUDI EKSPLORATIF PADA ORGANISASI ULU APAD DI DESA BUAHAN KAJA, GIANYAR ) - Putri, Elsa Savira; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 2 (2018), 2018)
ABSTRACT   Ulu Apad Organization is one of the traditional organizations in Bali which specializes in religious concern especially praying to the god. In Bali Ulu Apad begins since 200 M. In an organization, communication is an essential part which can determine the existence of the organization. Determining a certain communication patterns used in an organization means the communication process can be determined. The purpose of this study was to determine the communication pattern of the traditional organization of Ulu Apad in Buahan Kaja Village, Gianyar Regency. The study referred to the experiment by Leavit (1951) who divided the communication pattern into 5 parts, namely round pattern, chain pattern, wheel pattern, Y pattern and all channeled pattern. This study was qualitative study. The technique in determining the informans was purposive. The data obtained from the result of interviews, observation and documentation study. The technique used in analyzing the data was interactive analysis model from Miles & Huberman. The results showed that there was a different communication pattern in every activity of Ulu Apad organization; that is, in the formal meeting, the communication pattern used was Y pattern, in preparing malang, the pattern used was all channel pattern. Additionally, in the activity of making the lauk urap and serving malang offering, the pattern used was the wheel pattern.   Keywords: Communication Pattern, The Traditional Organization of Ulu                    Apad, Organizational Communication